COVID-19 lockdowns' effects on the quality of life, perceived health and well-being of healthy elderly individuals: A longitudinal comparison of pre-lockdown and lockdown states of well-being. (March 2022) - Colucci, E.; Nadeau, S.; Higgins, J.; Kehayia, E.; Poldma, T.; Saj, A.; de Guise, E.
Highlights: Lower quality of life, perceived health, and well-being during than pre-lockdown. No difference between the two lockdown periods. Quality of life linked to physical activity, happiness, and energy. Perceived health linked to exercise, medical condition, isolation, and memory. Well-being linked to isolation, energy, and age. Abstract: Purpose: . The concept of lockdown in relation to COVID-19 is thought to have an indirect impact on the quality of life and well-being of the elderly due to its consequences on the physical, psychological, and cognitive health of individuals. However, previous published studies on this subject are limited in terms of methodological approach used, including the absence of pre-confinement status and the type of experimental design, which is often cross-sectional. The present study proposes a longitudinal design with pre-confinement measures. It assesses changes in quality of life, perceived health, and well-being by comparing the period before lockdown (T1 = December 2019), three months after the start of the first lockdown (T2 = June 2020), and during the second lockdown (T3 = January 2021) due to COVID-19. Materials and Methods: . This study is conducted with a group of 72 healthy elderly persons. They completed an electronic (online) survey assessing personal factors, activities, and participation as well as responding to the EuroQol-5D and Warwick-Edinburgh Mental Well-being Scale. Results: . A decrease in quality of life, perceived health and well-being was observed between T1 and T2 and between T1 and T3, but no difference was reported between the two lockdown periods. The variables associated with these changes included energy level, level of happiness, physical activity, change in medical condition, memory difficulties, level of perceived isolation and age. Conclusion: . This study will help to target variables that may have a deleterious effect on older adults for consideration in future confinement settings and for preventive purposes.